Rural transformation in central Myanmar: Results from the rural economy and agriculture dry zone community survey - Belton, Ben; Filipski, Mateusz J.; Hu, Chaoran; Oo, Aung Tun; Htun, Aung (Michigan State University, 2017)
Public infrastructure development since 2011 has been extremely rapid, reflecting changing budgetary priorities at the union level. Sixty-five percent of rural electrification has occurred since this time, as has construction of more than half of secondary schools and 70% of public tubewells. Road infrastructure – already relatively good in comparison to other areas of the country – also improved during this period. Businesses offering transport services for goods and people have proliferated, reducing journey times from rural to urban areas and promoting greater mobility and market access. There has been a similar explosion in numbers of other off-farm enterprises, most notably those offering agricultural mechanization services, which have expanded with extreme rapidity. Brisk growth in numbers of non-farm enterprises providing goods and services for consumption (retailers, food sellers, etc.) has also taken place. The growth of both sets of businesses is associated with rapidly rising real rural wages, which increased by close to 40% between 2012 and 2014. This has created demand for labor saving technology in agriculture, and has increased consumer spending power. Access to credit has improved significantly, driven particularly by the expansion of loans provide by the Department of Cooperatives, and by microfinance institutions. This change has had a very significant impact on rates of interest charged on informal loans, which have fallen almost 5% per month since 2012.